Cervical detachment using monopolar SupraLoop™ electrode versus monopolar needle in laparoscopic supracervical hysterectomy (LSH): an interventional, comparative cohort study = Durchtrennung der Zervix mit der monopolaren SupraLoop™ Elektrode verglichen mit der monopolaren Nadelelektrode bei der laparoskopischen suprazervikalen Hysterektomie : eine interventionelle Kohortenstudie - Brucker, Sara; Rothmund, R.; Krämer, B.; Neis, F.; Schönfisch, B.; Zubke, W.; Taran, F. A.; Wallwiener, Markus (Geburtshilfe und Frauenheilkunde, 2013)
Objective: Currently available monopolar loop electrodes are difficult to handle in laparoscopic supracervical hysterectomy (LSH) and are entirely disposable devices, generating additional operating costs. The aim of this interventional study was the comparison of the efficiency and safety of cervical detachment with a newly developed monopolar loop electrode (SupraLoop™) with a conventional method of cervical detachment in LSH. Material and Methods: Our study sample included 1598 patients; 1070 patients that underwent LSH with cervical detachment using the monopolar SupraLoop™ (study group) and 528 patients that underwent LSH with cervical detachment using the monopolar needle (control group). We also assessed cervical detachment time and total device application and cutting time in a subgroup of 49 patients (23 patients from the study group and 26 patients from the control group).Results: Total operation time for LSH was significantly shorter among SupraLoop™ patients (93 ± 41 minutes) when compared to patients in whom cervical detachment was performed with the needle (105 ± 44 minutes) (p < 0.001). Cervical detachment time and total device application including cutting time was significantly shorter for the SupraLoop™ group (SupraLoop vs. needle; 0.12 ± 0.21 min vs. 5.1 ± 4.4 min [p < 0.001]; 2.3 ± 1.8 min vs. 5.4 ± 2.4 min [p < 0.001]). There were no major or minor complications directly related to the use of the SupraLoop™ device, whereas two intraoperative complications were directly related to the application of the monopolar needle. Conclusion: The newly developed monopolar loop electrode (SupraLoop™) is both an effective and safe instrument for cervical detachment in laparoscopic supracervical hysterectomy, and performed better than the needle, offering a significantly shorter operating time and less complications for the hysterectomy compared to the conventional method.